Flavonoid Levels in Beluntas Leaves (Pluchea indica (L.) Less) in Lamongan Regency Using a Spectrophotometer UV-Vis - Faizatul Fitria; Farida Noor Arifah; Prima Agusti Lukis; Sofira Dwi Meylinda Sari (Jurnal Ilmiah Sains, 2025)
The beluntas plant (Pluchea indica (L.) Less) is one of the Indonesian medicinal plants that is rich in secondary metabolite compounds, one of which is flavonoids. The level of flavonoid compounds in beluntas leaves (Pluchea indica (L.) Less) is quite large, around 2.79%. Flavonoids in beluntas leaves provide the greatest biological activity at 63.1%, and can be used for health. The purpose of this study is to determine the total flavonoid levels of beluntas leaf extract from Lamongan regency using Spektrophotometer UV-Vis with quersetin as standart. The extraction method used is maceration with 70% ethanol solvent and the ratio of simplicia and solvent is (1:5). The presence of flavonoid compounds was determined by qualitative tests using concentrated HCl reagents and Mg powder. Total flavonoid levels were analyzed using a UV-Vis spectrophotometer with a quercetin standard measured at a wavelength of 408 nm for 2 minutes. Positive results are shown from qualitative tests by a change in orange color. The beluntas leaf extract obtained was 56.024 grams with a yield of 14.006%. The total flavonoid content from measurements using a UV-Vis spectrophotometer was 6.522%. Keywords: Beluntas leaves; flavonoids; maceration; secondary metabolites; Spectrophotometer UV-Vis